Traditional Education of Indigenous Midwives in Yoruba-land: A Case Study in Oyo town. - Agboh, Veronica Aina (Obafemi Awolowo University, 2014)
This study was designed to investigate the training curriculum of indigenous midwives in Yorubaland. Data were collected through the use of a semi-structured interview schedule or the pre-requisites for training, duration of training, course content examination and graduation in traditional midwifery from practicing indigenous midwives in Oyo town.